Generic anthropometric and performance characteristics among elite adolescent boys in nine different sports - Pion, J.; Philippaerts, R.; Vaeyens, R.; Lenoir, M. (Science & Sports, 2014)
Introduction: The aim of the present study is to evaluate the Flemish Sports Compass, a non-sport specific generic testing battery, developed to guide children and adolescents towards (a) sport(s) discipline(s) they possess the right characteristics for. It is hypothesized that the set of 22 generic tests will have sufficient discriminant power to allocate athletes to their own sport based on a unique combination of test scores [1,2]. Methods: Anthropometry, physical fitness and motor coordination in 141 boys under 18 (16.1 ± 0.8 years) and post-age at peak height velocity (maturity offset = 2.674 ± 0.926) from Flemish Top Sport Academies for badminton, basketball, gymnastics, handball, judo, soccer, table tennis, triathlon and volleyball were evaluated. Sequential discriminant analyses were used to assess to what extent the scores on non-sport specific test allow the classification of young athletes as participants/non-participant in the respective sports. Results: Discriminant analyses resulted in a 96.4% correct classification of all participants for the nine different sports. When focusing on relevant performance characteristics, 80.1% to 97.2% of the total test sample was classified correctly within their respective disciplines. The discriminating characteristics are briefly the following: flexibility in gymnastics, explosive leg strength in badminton and volleyball, speed and agility in badminton, judo, soccer and volleyball, upper body strength in badminton, basketball and gymnastics, cardiorespiratory endurance in triathletes, dribbling skills in handball, basketball and soccer and overhead throwing skills in badminton and volleyball. Conclusions: The Flemish Sports Compass shows differences in generic talent characteristic distinguishing adolescent boys to their particular sport. The implications of these findings for talent programs are discussed, the most relevant being that a generic test battery might be useful in the orientation towards the sport that best fits the child/adolescent's characteristics.